Who cares for the carer? Codesigning a carer health and wellbeing clinic for older care partners of older people in Australia - Natasha Layton; Aislinn Lalor; Susan Slatyer; Den‐Ching A Lee; Christina Bryant; Moira Watson; Anjali Khushu; Elissa Burton; Déborah Oliveira; Natasha L. Brusco; Alessandro Jacinto; Elizabeth Tiller; et al. (Wiley, 2023)
Abstract Introduction Older carers or 'care partners' of older people experiencing care needs often provide essential support, at times while neglecting their own health and well‐being. This is an increasingly frequent scenario due to both demographic changes and policy shifts towards ageing in place. Multiple community stakeholders within the care and support ecosystem hold valuable expertise about the needs of older care partners, and the programme and policy responses that may better support their health and well‐being. The aim of this study was to identify the perspectives of stakeholders obtained through the codesign phase of a multicomponent research project investigating new models of care and support for older care partners suitable for the Australian context. Methods Principles of codesign were used to engage a purposeful sample of older care partners, health professionals, researchers, policy makers and health service administrators. Participants took part in a series of three codesign workshops conducted remotely via video conferencing. The workshops were supported with briefing material and generated consensus‐based summaries, arriving at a preferred service model. Findings This paper reports the research design and structure of the codesign panels, the range of findings identified as important to support the health and well‐being of older carers of older people, and the resulting service model principles. The codesigned and preferred model of care is currently being prepared for implementation and evaluation in Australia. Public Contribution This study was conducted using codesign methodology, whereby stakeholders including older care partners and others involved in supporting older carers, were integrally involved with design, development, results and conclusions.